MODEL PENDIDIKAN KARAKTER BERBASIS KEUNGGULAN LOKAL DAN GLOBAL DI MAN PURWOREJO - Sururiyah, Siti Khusniyati; Irma, Cintya Nurika (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2020)
This study aims to describe and explain (1) the concept of educational unit level curriculum development in MAN Purworejo, (2) the character education model in lessons based on local and global excellence in MAN Purworejo, and the advantages and disadvantages of local and global excellence-based education in MAN Purworejo (3). This research is a qualitative research approach to humanistic educational psychology theory. Data collection techniques used interview techniques, passive participation observation techniques, and documentation techniques. The results showed that the character education model in MAN Purworejo can be seen from the values forming character education in local and global excellence-based learning in MAN Purworejo. First, learning by synergizing the values of religion, culture, and individual potential. Second, learning that educates knowledge that leads to hard skills and soft skills. Third, efforts need to be made to develop, change, improve the atmosphere of all positive school citizens by using core values of hard work, quality improvement, honesty, efficiency and democracy.